2004
DOI: 10.1111/j.1572-0241.2004.30822.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Duodenal Acid Exposure and Its Relationship to Symptoms in Functional Dyspepsia with Prominent Nausea

Abstract: BACKGROUND: Duodenal hypersensitivity to acid and decreased duodenal clearance of exogenous acid have been reported in functional dyspepsia (FD). However, the relevance of these abnormalities to spontaneous duodenal acid exposure and dyspeptic symptoms in FD is unknown. AIMS:To determine spontaneous duodenal acid exposure and its relationship with symptoms, duodenal sensitivity to acid, and the effects of a 5-HT 3 receptor antagonist on duodenal responses to acid in FD. METHODS:Eleven FD patients with prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(122 citation statements)
references
References 46 publications
6
114
0
2
Order By: Relevance
“…23,24 In fact, several groups have reported increased sensitivity of the duodenum to infused acid. 25,26 However, the precise mechanism for the acid-induced postprandial symptoms is unclear. Tack and colleagues demonstrated that high concentrations of acid were associated with significant changes in motor function such as increased fundic tone or induction of migrating motor complex (MMC)-like activity that could conceivably alter thresholds for sensation to distensions of the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In fact, several groups have reported increased sensitivity of the duodenum to infused acid. 25,26 However, the precise mechanism for the acid-induced postprandial symptoms is unclear. Tack and colleagues demonstrated that high concentrations of acid were associated with significant changes in motor function such as increased fundic tone or induction of migrating motor complex (MMC)-like activity that could conceivably alter thresholds for sensation to distensions of the fundus.…”
Section: Discussionmentioning
confidence: 99%
“…Functional dyspepsia symptoms after duodenal acid infusion 74 could result from sensitization of transient receptor potential cation channel subfamily V member 1 (TRPV1) or decreased acid clearance from Box 1 | Rome IV symptom criteria for functional dyspepsia and its subtypes*…”
Section: Gastroduodenal Sensitivitymentioning
confidence: 99%
“…Furthermore, recent studies have suggested a role for increased duodenal acid exposure or hypersensitivity to duodenal acid in the pathogenesis of functional dyspepsia. 53,54 In patients with duodenal acid hypersensitivity, a tendency toward a decrease of duodenal acid hypersensitivity was observed after 2 weeks of proton pump inhibitor treatment. However, potential benefits of acid-suppressive treatment of functional dyspepsia patients with increased duodenal acid exposure remain to be defined.…”
Section: Acid-suppressive Drugsmentioning
confidence: 99%
“…[47][48][49][50] Other Mechanisms A number of other pathophysiologic mechanisms have been implicated in the pathophysiology of functional dyspepsia, based on limited numbers of studies, generally in small groups of patients. These include duodenal hypersensitivity to lipids, 51,52 increased duodenal acid exposure due to impaired duodenal clearance, 53,54 lack of postprandial suppression of phasic contractility of the proximal stomach, 55 and abnormalities of gastric electrical rhythm. 56,57 …”
Section: Helicobacter Pylori Infectionmentioning
confidence: 99%